CDK4/6 inhibitors induce senescence in the breast cancer cell lines with enhanced anti- tumor immunogenic properties compared with DNA-damaging agents - 이동현 (The Graduate School, Ajou University, 2024)
CDK4/6 inhibitors induce senescence in the breast cancer cell lines with enhanced anti-tumor immunogenic properties compared with DNA- damaging agents Understanding the phenomenon of senescence during cancer treatment remains controversial, yet crucial for comprehending its impact on tumor suppression or activation. Therefore, this study aims to compare and analyze the senescence status of breast cancer cells induced by various chemotherapeutic agents (DNA-damaging agents and CDK4/6 inhibitors). Although these agents induce a similar extent of senescence, it has been identified and observed that senescence-associated secretory phenotype (SASP), which promotes inflammatory cytokines (TGFβ, TNFA and IL-6), pro-tumorigenic immunity (CXCL2, CXCL8 and CSF1), and pro-angiogenic factors (VEGF family and GDF15), are more robust in senescent tumor cells induced by DNA-damaging agents. Interestingly, senescent tumor cells induced by cyclin- dependent kinase4/6 inhibitors (CDK4/6i) not only exhibit increased expression of SASP and ligands associated with anti-tumor immunity (HLA family and B2M) but also release chemokines (CXCL9, 10, and 11) into the tumor microenvironment (TME) to enhance immune surveillance and recruit NK and T cells compared to DNA- damaging agents. Despite the deficient activation of Nuclear Factor-Kappa-B (NF-κB) and p53 pathway in CDK4/6i-induced senescence, SASP expressions are still comparable to those of DNA-damaging agents-induced senescence. Overall, this study shows that tumor cells treated with various types of agents elicit senescence to similar extents, while the expressions of pro-tumorigenic and anti-tumorigenic SASP vary substantially between the agents, depending on the type of chemotherapeutic agents used. Thus, TIS by CDK4/6i may serve as an effective approach for treatment strategies in cancer patients by utilizing the distinct characteristics of senescence. Keywords: Therapy-induced senescence, CDK4/6 inhibitors, DNA-damaging agents, Senescence-associated secretory phenotype, Tumor microenvironment
학위논문(박사)--의생명과학과,2024. 8
Keywords: CDK4/6 inhibitors; DNA-damaging agents; Senescence-associated secretory phenotype; Therapy-induced senescence; Tumor microenvironment